Tiempos y mujeres de Santa Fe, Ciudad de México - Ortiz Madariaga, Laura Eugenia (El Colegio de México, 2017)
This paper approaches the way to understand women’s identities from diverse territorial units departing from the way they use and perceive time. We focus on women living in neighboring territorial units, but with many dissimilarities: towns absorbed by the city, popular neighborhoods and middle-class neighborhoods. The article describes the theoretical-methodological frame used to approach time and the temporal dimension. A gender perspective is emphasized, since time use patterns are strongly linked to the idea of being a man or a woman. In addition, markers of generational and social class also have an influence on how time is used.